2013
DOI: 10.5194/bgd-10-16043-2013
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential effects of extreme drought on production and respiration: synthesis and modeling analysis

Abstract: Extremes in climate may severely impact ecosystem structure and function, with both the magnitude and rate of response differing among ecosystem types and processes. We conducted a modeling analysis of the effects of extreme drought on two key ecosystem processes, production and respiration, and to provide broader context we complemented this with a synthesis of published results across multiple ecosystems. The synthesis indicated that across a broad range of biomes gross primary production (GPP) genera… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 63 publications
6
56
0
Order By: Relevance
“…Climatic stresses affected photosynthesis and respiration differentially (Shi et al, 2014). In general, GPP was more sensitive to drought than RE (Schwalm et al, 2010).…”
Section: Relative Contribution Of Be To the Iav In C Fluxes At The Ecmentioning
confidence: 94%
See 1 more Smart Citation
“…Climatic stresses affected photosynthesis and respiration differentially (Shi et al, 2014). In general, GPP was more sensitive to drought than RE (Schwalm et al, 2010).…”
Section: Relative Contribution Of Be To the Iav In C Fluxes At The Ecmentioning
confidence: 94%
“…while heterotrophic respiration was a C pool-controlled process at the situation of long-term drought (Shi et al, 2014). In addition, although the thermal acclimation of photosynthesis and respiration was found widely at both species and ecosystem scales, the different responses of these two processes to low temperature have not been well studied (Atkin and Tjoelker, 2003;Way and Yamori, 2014;Niu et al, 2012).…”
Section: Relative Contribution Of Be To the Iav In C Fluxes At The Ecmentioning
confidence: 99%
“…These authors showed in a climate chamber experiment that rewetting by rain may be too brief for peatmoss to offset the autotrophic respiration cost associated with restarting their photosynthetic machinery. From other ecosystems, it is known that rain frequency, intensity and duration may have a larger impact on key carbon cycling processes than the total rain amount, indicating that rain characteristics are important controls on the carbon balance (Knapp et al, 2002;Shi et al, 2014;Xu et al, 2013). Small rain events may, for example, trigger short-term bursts of heterotrophic respiration in semi-arid ecosystems due to increased water and substrate availability, whereas larger rain events may also stimulate photosynthesis (Lee et al, 2004;Schwinning & Sala, 2004;Unger et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Different sensitivity of GPP and R e to those 2 months reflects the complex relationship between carbon exchange and varying intensity of precipitation ( Figure 11; Ciais et al, 2005;Resco et al, 2009;Jentsch et al, 2011;Shi et al, 2014). As the balance between GPP…”
Section: Resultsmentioning
confidence: 99%